An Immersion to Appreciate a Hilma af Klint Art Using Kids Playfulness - Scoz, Emanuella (2025)
This article present a pedagogical activity developed for art classes, applied to two classes of the first full year of elementary school, initial years, in two schools in the municipality of Indaial, in Santa Catarina state, Brazil. One being a rural school with eight students and a central school with 25 students. The article present the format for preparing and applying the activity, from a playful perspective, seeking to broaden students' focus on the appreciation of works of Art, deepening the generation of knowledge and children's affective experience with Art. Hilma af Klint was selected for the activity, due to the breadth of visual elements in her works. From the application of the activity, it was observed that the most appropriate method for applying the activity would be the “SIR” approach. And the analysis of the results was carried out using participant observation methodology. The results obtained demonstrated that the children were immersed, their focus was expanded by their own curiosity, expanding their affections.